An Experimental Approach to Exploring Market Responses in Small-Scale Fishing Communities - Drury O’Neill, Elizabeth; Lindahl, Therese; Daw, Tim; Crona, Beatrice; Ferrer, Alice Joan G.; Pomeroy, Robert (Frontiers in Marine Science, 2019)
Small-scale fishing communities are increasingly connected to international seafood trade via exports to a growing global market. Understanding how this connectedness impacts local fishery systems, both socially and ecologically, has become a necessary challenge for fisheries governance. Market prices are a potential mechanism by which global market demands are transferred to small-scale fishery actors. In most small-scale fisheries this happens through various traders (intermediaries, middlemen/women or patrons). By financing fishing operations, buying and selling products and transferring market information, traders can actively pass international market signals, such as price, to fishers. How these signals influence fishers' decisions and consequent fishing effort is still poorly understood yet significant for future social-ecological sustainability. The paper uses an economic framed field experiment, in combination with interviews, to shed light on this. It does so in the context of the Philippine patron-client 'suki' arrangement. Over 250 fishers in Concepcion, Iloilo were asked in an economic experiment, to make decisions about fuel loans in light of changing market prices. Interviews with participants and their patrons gathered additional information on relevant contextual variables potentially influencing borrowing. They included fisher characteristics and socio-economic conditions. Contrary to our hypotheses, fishers showed no response in their borrowing behaviour to experimental price changes. Instead, gender and the previous experiment round were predictive of their choice of loans in the experiment. We explore possible reasons for this.